A recovery‐based error estimator for finite volume methods of interface problems: Conforming linear elements. Issue 1 (3rd February 2012) - Mu, Lin; Jari, Rabeea; Conner, Loralyn
Abstract In this article, we present a recovery‐based a posteriori error estimator for finite volume methods which use the conforming linear trial functions to approximate elliptic interface problems. The reliability and efficiency bounds for the error estimator are established by recovering the flux from a weighted L2 projection to H(div) conforming finite element spaces. Numerical experiments are given to support the conclusions. © 2012 Wiley Periodicals, Inc. Numer Methods Partial Differential Eq 2013